The extent of compliance with Republic Act 6966 among public school libraries and government agencies in Region VI - Hormillosa, Ma. Aida F. (2002)
The study aimed to find out the extent of compliance with R.A. 6966 among public school libraries and government agencies in Region VI.A survey questionnaire was constructed to determine the following: 1. The profile of professional librarians employed in the libraries; 2. To find out how many librarians employed in the libraries are licensed; Assess R. A. 6966's contribution in upgrading the librarian's status after passing the licensure examination and in recognizing them as professionals.